The dynamics of international migration: Introduction - Oded Stark (International Review of Economics and Finance, 2013)
This special issue of the International Review of Economics and Finance contributes to the received literature of the dynamics of international migration by highlighting the role of tradition in propelling migration; by admitting that the human capital formation response to the prospect of migration is gradual; by studying the impact of such formation on economic growth and welfare; by working out the consequences of the migration of parents for the wellbeing of their children; by demonstrating that the “basin of attraction” of new migrants includes cross-national past migrants; and by causally relating the intensity of the effort that migrants exert to assimilate economically to the extent of their social integration.
Keywords: D01; D62; F22; F24; I21; I30; J15; J22; J24; J43; J61; N3; N33; N34; N93; N94; O15; O40; Z10; 330; Poland-to-Germany seasonal migration; Evolution of seasonal migration; Long-term durability of seasonal migration; Tradition; Human capital formation; Migration; Brain drain; Externalities; Dynamics; Social welfare; Overlapping-generations growth model; Intertemporal human capital externalities; Long-run growth effect of the prospect of migration; Social welfare gains; Remittances; Child labor; Egypt; International migration; Cross-national pull effect; Aggregate migration data; Spain; Assimilation; Integration; Social proximity; Interpersonal comparisons; Relative deprivation